2017
DOI: 10.5935/abc.20170025
|View full text |Cite
|
Sign up to set email alerts
|

MMP-9 Levels and IMT of Carotid Arteries are Elevated in Obese Children and Adolescents Compared to Non-Obese

Abstract: BackgroundChildhood obesity is associated with increased risk of atherosclerosis and cardiovascular disease in adulthood. Increased intima-media thickness (IMT) of the carotid artery is linked to the initiation and progression of the chronic inflammatory processes implicated in cardiovascular disease. Matrix metalloproteinase-9 (MMP-9) plays an important role in the degradation of the extracellular matrix and, consequently, in the development, morphogenesis, repair and remodeling of connective tissues.Objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…This inflammation leads to the secretion of many biochemical markers known to augment the risk for plaque fissuring and adverse cardiovascular outcomes in adults . In children, CXCL8, MPO, MMP‐8 and MMP‐9 levels have been shown to be higher in children with obesity compared to children with normal weight, MMP‐9 being higher in hypertensive than in nonhypertensive children with obesity and MPO correlating with cardiovascular risk factors . In our study, although there was no control group of children with normal weight to compare biomarkers levels, their relationship with cardiovascular health indicators, such as blood pressure and vascular function, was examined.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This inflammation leads to the secretion of many biochemical markers known to augment the risk for plaque fissuring and adverse cardiovascular outcomes in adults . In children, CXCL8, MPO, MMP‐8 and MMP‐9 levels have been shown to be higher in children with obesity compared to children with normal weight, MMP‐9 being higher in hypertensive than in nonhypertensive children with obesity and MPO correlating with cardiovascular risk factors . In our study, although there was no control group of children with normal weight to compare biomarkers levels, their relationship with cardiovascular health indicators, such as blood pressure and vascular function, was examined.…”
Section: Discussionmentioning
confidence: 65%
“…One pediatric study performed in older subjects with obesity showed that MMP-9 levels and IMT of the carotid arteries were higher compared to a control group and that they were correlated to each other. 25 To our knowledge, no other study has investigated the relationship between biomarkers and vascular function, especially in pre-pubertal children with obesity.…”
Section: F I G U R E 1 a Mmp-8 Concentrations'mentioning
confidence: 99%
“…In this context, considering a close association among childhood obesity, serum MMP-9 and vit D levels, the correlation of this study’s result 1 with serum vit D levels might be beneficial.…”
mentioning
confidence: 91%
“…I have read the article entitled “MMP-9 Levels and IMT of Carotid Arteries are Elevated in Obese Children and Adolescents Compared to Non-Obese” by Andrade et al 1 , recently published in journal, with great interest. The investigators reported that obese children and adolescents present higher mean intima-media thickness (IMT), plasma matrix metalloproteinase (MMP)-9 and MMP-9/tissue inhibitor of metalloproteinase-1 ratio compared to the non-obese.…”
mentioning
confidence: 99%
See 1 more Smart Citation